Pemanfaatan tanaman obat untuk pengendalian penyakit dalam usaha budidaya - Schram, Shifa A. (e-Journal BUDIDAYA PERAIRAN, 2017)
Production of global and national aquaculture often fails due to outbreaks of fish diseases caused by viruses, bacteria, fungi and parasites. Moreover, as a tropical country, Indonesia has a climate that strongly supports the development of pathogens. The occurrence of disease outbreak is basically as a result of disturbance of the balance interaction between fish, the unfavorable environment and pathogens. Medicinal plants are rich of antimicrobial compounds such as naphthoquinone, coumarin derivatives, tannins, flavonoids, and steroids, which are effective for inhibiting the growth of bacteria and fungi. Oleoresin compounds, i.e. essential oils that act as antibacterial and antifungal are also present in medicinal plants. Medicinal plants also serve to stop the bleeding, because there are anti-inflammatory compounds (anti-inflammatory). This compound is found in several medicinal plants that have been tested to cope with fish diseases such as rose balsam, guava leaf, garlic, betel leaf and ginger. Some of the advantages of using traditional medicinal plants are relatively safe, easy to obtain, cheap, not resistant, and relatively harmless to the surrounding environment and do not create antibiotic-resistant pathogens. Thus, it is more adviseable to use medicinal plants in controlling fish diseases.Â Keywords: medicinal plants, aquaculture, aquaculture, fish diseases